Implementation of chain story techniques to improve english speaking ability at imanuel YPK vocational high school, Sorong City - Lulu Jola Uktolseja; Sherly Gaspersz (Journal of Education and Learning (EduLearn), 2019)
The function of English as the international language that connects various countries with different languages makes English as an important communication tool to be learned and taught for students from various levels of education as the provision to face the current era of globalization. The chain story technique that implemented in this research, is a technique that is suitable to be used to teach students who have not dared to actively use English. This technique helps students of Imanuel YPK Vocational High School, Sorong City to work as a team and help each other to construct the sentence. This study was designed in the form of Classroom Action Research (CAR). The method of this research is a qualitative and quantitative method. The qualitative to explain the condition before and after the action. The quantitative to count the score of the students. As for the subject in this research is the Class X Automation and Office Management. This is done in order to obtain valid and reliable research data. Data collection techniques used were observation, test and interview. Results of the study showed that: (1) Based on the observation, the students are changed to be more brave and confident to speak English; (2) Based on the test, there is a very significant change towards the positive, when compared to the value of very good and good in cycle 1 which is 42% while in cycle 2 is 80%, so there is an increase of 38%; (3) Based on the interview, the students were happy and giving the good responses about the treatment and the progress they have done